Development of an Arabic Grammar Instructional Medium Based on Illustrated Stories in Elementary School - Siti Nurhayati Solihah; Moch Mu'izzuddin; Ahmad Habibi Syahid; Siti Nurislamiah; Nur Alfin Bintang Perkasa (Al-Muyassar: Journal of Arabic Education, 2026)
This study develops comic-based instructional media for Arabic grammatical learning at the elementary school level. The background of this research lies in the low interest and understanding of elementary students toward Arabic grammar due to conventional teaching methods and unattractive learning media. The objectives of this study are to investigate the actual condition of Arabic grammar learning before using comic media, to develop comic-based instructional media, to assess its feasibility, and to measure its effectiveness in improving students’ understanding. The theoretical foundation of this study is the importance of interactive visual media in supporting students’ cognitive processing (Clark & Mayer) as well as the need for media that are aligned with children’s characteristics. The research method applied is Research and Development (R&D) using the ADDIE model. The research subjects were fourth grade students of Muhammadiyah Elementary School 33 Kademangan, with research instruments including observation, interviews, expert validation in content and media, student response questionnaires, and pretest–posttest assessments. The findings revealed that the comic media obtained an excellent feasibility score from the content expert (92.5%) and the media expert (96.66%). Student responses were also very positive, with an average of 95%. The effectiveness of the media was evidenced by the increase in the average pretest score (54.57) to the posttest score (81.52), with an N-Gain value of 0.60 (categorized as moderate). This research contributes to the development of innovative instructional media that suit the characteristics of elementary school students and proves effective in enhancing their understanding of Arabic grammar.